DNA Binding and Cleavage Activity of Binuclear Metal Complexes with Benzil-α-Monoxime Thiosemicarbzone - M. S. Surendra Babu; T. B. Patrudu; K. Hussain Reddy (E-Journal of Chemistry)
Transition metal complexes of copper(II), nickel(II), cobalt(II) and iron(II) with benzil-α-monoxime thiosemicarbazone (BMOT) have been synthesized and characterized by molar conductance, magnetic moments, IR, electronic and ESR spectroscopy. Electrochemical behaviors of these complexes were investigated by cyclic voltammetric studies. The nuclease activity of these complexes has been investigated on double-stranded pBR322 circular plasmid DNA by using the gel electrophoresis experiments in presence and absence of oxidant (H2O2). In the absence of oxidant DNA cleavage by hydrolytically was observed a less discernable, whereas in presence of oxidant (H2O2) all complexes showed increased nuclease activity.